2008
DOI: 10.1002/qj.341
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the influence of observations on medium‐range forecasts of atmospheric flow

Abstract: ABSTRACT:In recent years, the Ensemble Transform Kalman Filter (ETKF) has been demonstrated to be useful for identifying a priori dynamically important locations for the placement of supplementary dropwindsonde observations aimed at improving short-range (1-3 day) forecasts of high-impact winter weather. In this paper, the ability of this strategy to predict the influence (or 'signal') of assimilating observations into the NCEP Global Forecast System for forecasts of 200 hPa wind up to 6 days is evaluated. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…The results of Sellwood et al (2008) and , which demonstrated that ETKF targets in the midlatitude storm track could be traced upstream out to 7 d in zonal flow regimes, are unlikely to be corroborated for TCs except in cases of a distinct and unambiguous interaction with an approaching midlatitude trough. This higher ambiguity in ETKF targets for TCs heightens the need for careful interpretation by field programme planners.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…The results of Sellwood et al (2008) and , which demonstrated that ETKF targets in the midlatitude storm track could be traced upstream out to 7 d in zonal flow regimes, are unlikely to be corroborated for TCs except in cases of a distinct and unambiguous interaction with an approaching midlatitude trough. This higher ambiguity in ETKF targets for TCs heightens the need for careful interpretation by field programme planners.…”
Section: Discussionmentioning
confidence: 87%
“…In the future, the examination of the un-normalized value of signal variance would be useful, in order to quantitatively estimate day-to-day changes in the potential for forecast-error reduction. The ETKF has shown promise in this regard in the midlatitudes (Majumdar et al, , 2002Sellwood et al, 2008). For tropical cyclones, it is not yet clear to the authors how to interpret quantitatively the reduction in forecast-error variance, given that it is largely a function of both the TC wind field and its position.…”
Section: Etkf Theory and Ensemble Perturbation Modificationmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, many Observing System Experiments (OSEs) have been conducted throughout the world to investigate the impacts of observations on analysis and forecast errors in downstream areas (e.g., Langland et al 1999;Szunyogh et al 2002;Langland 2005;Fourrie et al 2006;Wu et al 2007;Chou and Wu 2008;Sellwood et al 2008;Inoue et al 2009;Yamaguchi et al 2009). In addition, TIGGE has enabled us to obtain operational medium-range ensemble forecast data quasi-operationally (;2 day behind).…”
Section: Discussionmentioning
confidence: 99%